Journal of East Asian Linguistics - Huang, C. T. James; Kenstowicz, Michael; Saito, Mamoru; Simpson, Andrew; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The study of East Asian languages, especially of Chinese, Japanese and Korean, has existed for a long time as a field, as demonstrated by the existence of programs in most institutions of higher learning and research that include these languages as a major component. Speakers of these three languages have shared a great deal of linguistic heritage during the development of their languages through cultural contacts, in addition to possible genealogical linkage. These languages accordingly possess various common features. Another important factor that ties them together as a field is that they have shared a common tradition of linguistic scholarship, a tradition that distinguishes itself from the study of western languages. Against this tradition, much recent work has approached these languages from a broader perspective beyond the area, considering them within contexts of general theoretical research, bringing new lights to old problems in the area and contributing to current issues in linguistic theory. But there continues to be good reason for scholars working in this approach to hold a special interest in each other's work. Especially with the amount of most recent theoretical work on these languages, the field of theoretical East Asian linguistics has been fast growing. The purpose of the Journal of East Asian Linguistics is to provide a common forum for such scholarly activities, and to foster further growth that will allow the field to benefit more from linguistic theory of today, and enable the languages to play a more important role in shaping linguistic theory of tomorrow.
Keywords: Chinese language; Comparative linguistics; Japanese language; Philology; Linguistics; Comparative Linguistics; Japanese; Chinese; Theoretical Linguistics; Language and Literature